Strategi Creator Tiktok Dalam Membangun Kepercayaan Dan Minat Beli - Siti Nur Haliza (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze how TikTok content creators build trust and increase purchase intention from a user perspective. This study uses a qualitative approach by conducting in-depth interviews with TikTok users who actively watch product review content. The results show that there are several key strategies used by TikTok content creators in building trust and increasing purchase intention, such as using a hook at the beginning of the video to attract attention, communication that feels natural and not forced, and displaying authentic and consistent product reviews. Creators who show honest and consistent product usage experiences are considered more credible and have a greater influence on purchasing decisions than creators who only focus on entertainment.